Determination of Palladium and Platinum by Solid Phase Extraction and High Performance Liquid Chromatography - Hu, Qun; Li, Yinke; Yang, Bo; Hu, Lin; Ye, Yanqing; Hu, Qiufen (Asian Journal of Chemistry, 2012)
A new method for the determination of palladium and platinum ions using high performance liquid chromatography equipped with on-line solid phase extraction was developed. The palladium and platinum ions were derivatized with 2-(2-quinolinylazo)-1,3-diaminobenzene (QADAB) to form coloured chelate. The Pd-QADAB and Pt-QADAB chelates were then enriched on an enrichment column using a 0.05 mol L-1 of phosphoric acid as mobile phase. After the enrichment was completed, the retained chelates were back-flushed to the analytical column. The separation of chelates on the analytical column [CQUITY UPLC BEH C18 (1.7 μm 4.6 × 50 mm)] was satisfactory when 40 % acetonitrile (containing 0.05 mol L-1 of phosphoric acid and 0.1 % of triton X-100) was used as mobile phase. The Pt-QADAB and Pd-QADAB chelates were separated completely within 2.5 min. The detection limits (S/N = 3) for palladium and platinum were 1.0 ng L-1 and 1.2 ng L-1, respectively. The method was applied to the determination of palladium and platinum in water samples with good results.